Utilization of Several Industrial Wastes as Raw Material for Calcium Sulfoaluminate Cement - Phongthorn Julphunthong (Materials, 2019)
The aim of this research was to study the production of calcium sulfoaluminate (CSA) cement from several industrial waste materials including with marble dust waste, flue gas desulfurization gypsum, ceramics dust waste, and napier grass ash. The chemical composition, microstructure, and phase composition of raw materials were examined using energy dispersive X-ray fluorescence (EDXRF), scanning electron microscopy (SEM), and X-ray diffraction (XRD), respectively. All raw wastes were analyzed using their chemical composition to assign proportion for raw mixture. The raw mixture is calcined at controlled calcination temperatures ranging from 1200 °C to 1300 °C for 30 min. Subsequently, with analysis, their phase composition is calculated by the Rietveld refinement technique. The results suggested that phase composition of clinker calcined at 1250 °C shows the closest composition when compared to target phases, and was selected to prepare CSA cement. The FTIR analysis was performed to study the hydration processes of CSA cement. The Ordinary Portland cement (OPC) based with adding CSA cement between 20 wt.% and 40 wt.% were investigated for the effect of CSA cement fraction on water requirement, setting times and compressive strength. The results showed that rapid setting and high early strength can be achieved by the addition of 20−40 wt.% CSA cement to OPC.